The Effect of Systemic Parameters and Baseline Characteristics in Short-Term Response Analysis with Intravitreal Ranibizumab in Treatment-Naive Patients with Neovascular Age-Related Macular Degeneration - Laura García-Quintanilla; Pablo Almuiña-Varela; María José Rodríguez-Cid; María Gil-Martínez; Maximino J. Abraldes; Francisco Gómez-Ulla; Miguel González-Barcia; Cristina Mondelo-García; Ana Estany-Gestal; Francisco J. Otero-Espinar; Maribel Fernández-Rodríguez; Anxo Fernández-Ferreiro (MDPI AG, 2024)
Anti-vascular endothelial growth factor drugs keep being the main therapy for neovascular age-related macular degeneration (AMD). Possible predictive parameters (demographic, biochemical and/or inflammatory) could anticipate short-term treatment response with ranibizumab. 46 treatment-naive patients were included in a prospective observational study. They underwent three monthly injections of intravitreal ranibizumab for neovascular AMD and the clinical examination was made at baseline and one month after the third injection. Demographic characteristics, co-morbidities and concomitant treatments were recorded at the baseline visit. Biochemical parameters, complete blood count and inflammation biomarkers were also measured at these times. Uric Acid was found to be statistically significant with a one-point difference between good and poor responders in both basal and treated patients, but only in basal parameters was statistical significance reached (p = 0.007 vs. p = 0.071 in treated patients). Cholesterol and inflammatory parameters such as white blood cell count and neutrophils were significantly reduced over time when treated with intravitreal ranibizumab. On the other hand, women seemed to have a worse prognosis for short-term response to intravitreal ranibizumab treatment. Uric acid may help identify possible non-responders before initial treatment with ranibizumab, and cholesterol and white blood cells could be good candidates to monitor short-term response to ranibizumab treatment.